Biologically recycled continental iron is a major component in banded iron formations - Li, Weiqiang; Brian L. Beard; Clark M. Johnson (Proceedings of the National Academy of Sciences - PNAS, 2015)
Banded iron formations (BIFs) record a time of extensive Fe deposition in the Precambrian oceans, but the sources and pathways for metals in BIFs remain controversial. Here, we present Fe- and Nd-isotope data that indicate two sources of Fe for the large BIF units deposited 2.5 billion y ago. High-Îµ Nd and -Î´ âµâ¶Fe signatures in some BIF samples record a hydrothermal component, but correlated decreases in Îµ Nd- and Î´ âµâ¶Fe values reflect contributions from a continental component. The continental Fe source is best explained by Fe mobilization on the continental margin by microbial dissimilatory iron reduction (DIR) and confirms for the first time, to our knowledge, a microbially driven Fe shuttle for the largest BIFs on Earth. Detailed sampling at various scales shows that the proportions of hydrothermal and continental Fe sources were invariant over periods of 10 â°â10 Â³ y, indicating that there was no seasonal control, although Fe sources varied on longer timescales of 10 âµâ10 â¶ y, suggesting a control by marine basin circulation. These results show that Fe sources and pathways for BIFs reflect the interplay between abiologic (hydrothermal) and biologic processes, where the latter reflects DIR that operated on a basin-wide scale in the Archean.